Dinâmica da comunidade de macroinvertebrados bentônicos no baixo rio Xingu durante a fase inicial de operação da Usina Hidrelétrica (UHE) de Belo Monte - Assis, João Vitor de Mello (Universidade Federal de São Carlos, 2018)
The Belo Monte Hydroelectric Power Plant started operations in 2016 in the lower Xingu River basin. Dams in the Amazon have many social and environmental impacts and there is a prerspective of changes in river hydrological regimes due to climate change. In this contexto, benthic macroinvertebrates are important organisms in the functioning of freshwater ecosystems and are also widely used in water quality monitoring. In the present study, 11 sampling points were selected in different basin environments to evaluate the parameters of surface water and sediment, benthic community dynamics and application of a biological index (BMWP) to classify water quality during the initial phase of hydroelectric operation. Surface water and sediment analyses did not indicate impacts directly associated with damming, but the dynamics of benthic macroinvertebrates and BMWP indicated changes in the ecosystem. In the year 2016 a severe drought occurred and its combination with the modifications in the basin negatively affected the benthic community. The natural pulses at the water level along the hydrological cycle in the Xingu River are a force function that drives density and richness of benthic macroinvertebrates and their own characteristics in the composition of that community are associated with the discordant result of the BMWP. An alternative in monitoring would be the use of diversity indexes related to the natural dynamics of the community. The minimum flow in the river should be maintained and there should exist protection around water bodies throughout the basin.
Dynamics of the benthic macroinvertebrate community in the lower Xingu River during the initial phase of operation of the Belo Monte Hydroelectric Power Plant (HPP)
Keywords: Macroinvertebrados bentônicos; Bacia Amazônica; Usina hidrelétrica; Estiagem; Pulso de inundação; Benthic macroinvertebrate; Amazon basin; Hidroelectric power plant; Drought; Flood pulse; CIENCIAS BIOLOGICAS::ECOLOGIA